2000
DOI: 10.1046/j.1365-2141.2000.01949.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric and functional characterization of AC133+ cells from human umbilical cord blood

Abstract: Summary. AC1331 cells may represent an alternative source of transplantable haemopoietic progenitor cells to CD34 1 cells. Here, we have addressed the characterization of umbilical cord blood (UCB) AC1331 cells and compared their immunophenotypic and functional features with those of UCB CD34 1 cells. UCB AC133 1 and CD34 1 cell fractions were purified by magnetic cell sorting, analysed by flow cytometry, tested for their content in blast cell colonyforming units (CFU-Bl), erythroid and granulocyte±macro-phage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…31 Although all cultures were performed with a starting population of CD133 + /CD34 + cells independent of the culture conditions, a balance between 3 different proportions of SC subpopulations, CD133 + /CD34 + , CD133 + / CD34 − and CD133 − /CD34 + , was established after expansion. The CD133 − /CD34 + fraction has been described by other groups as part of the CD34 + SC fraction (~23% of the total number of CD34 + cells in cord blood) with reduced clonogenic potential.…”
Section: Discussionmentioning
confidence: 99%
“…31 Although all cultures were performed with a starting population of CD133 + /CD34 + cells independent of the culture conditions, a balance between 3 different proportions of SC subpopulations, CD133 + /CD34 + , CD133 + / CD34 − and CD133 − /CD34 + , was established after expansion. The CD133 − /CD34 + fraction has been described by other groups as part of the CD34 + SC fraction (~23% of the total number of CD34 + cells in cord blood) with reduced clonogenic potential.…”
Section: Discussionmentioning
confidence: 99%
“…For reprints contact: Reprints@AlphaMedPress.com 101 hosts [3,5]. CD133 was reported as an alternative marker for positive selection methods targeting more primitive HSPC enriched with CD34 bright cells [6,7]. However, we have recently reported that although CD133 + cells had interesting ex vivo expansion potential, they still encompassed cells at various stages of differentiation [8].…”
Section: ® Original Articlementioning
confidence: 99%
“…CD133 + stem cells with erythroid potential represent mostly an immature subpopulation of CD34 + stem cells with erythroid potential [18][19][20][21][22][23][24]. Figure 5 compares the differential effects of IL-3 and anti-TGF-β on these subpopulations.…”
Section: Effects Of Il-3 and Anti-tgf-β β On Different Stem Cell Subpmentioning
confidence: 99%
“…We focused on CD133 + stem cells with erythroid potential, most of which represent a large immature subpopulation of CD34 + cells [18][19][20][21][22][23][24], because our preliminary tests showed them to be more responsive than the remaining CD133 -CD34 + population to neutralizing anti-TGF-β antibodies as well as to the early-acting cytokine interleukin-3 (IL-3). Using a sensitive flow cytometric method that can detect very low levels of cellular globin contents [25,26], we monitored the effects of neutralizing anti-TGF-β antibodies, applied during the first few days of stem cell development, on the subsequent proliferation and globin expression of erythroid progenitors.…”
Section: ® Original Articlementioning
confidence: 99%